All you need is guitar pedals: The communicative construction of material culture in YouTube product reviews. (October 2022) - Gibson, Will
Abstract: Through an interactionist analysis of guitar pedal review videos this paper explores the communicative practices of product reviewing in YouTube. Focussing on one guitar pedal, the analysis reveals how reviewers positioned the pedal as an 'idealised object' and as part of the 'material good life' of guitarists. Reviewers' communicative strategies projected a sense of shared intersubjective experience of the pedal by bracketing out issues of knowledge, skill, and access to technology, and by constructing the vloggers' credentials as reviewers. This analysis contributes to our understanding of the structures of consumer cultures on YouTube, showing how reviewers communicatively construct audiences, products, themselves, and, more generally, the practices of material culture use in this specific art world. I argue that the interactionist perspective adopted here is an important and under-used framework for analysing consumer culture, and that it helps us to see how material culture is manufactured as a discursive, communicative act through the mundane activities of reviewing.